Electoral systems in divided societies : the Fiji constitution review - Lal, Brij V.; Larmour, Peter (PANDORA electronic collection., 2012)
In 1987, Fiji had its first change of government since the country became independent in 1970. ... A new Constitution was drawn up to replace the one adopted at Independence in 1970. ... The 1990 Constitution contained provisions for its own review within seven years (Section 161). The Review was eventually 2 commissioned in March 1995, and reported in September 1996. ... The chapters in this book assess the CRC's recommendations about the system of electing members of Parliament. ... The following chapters are based on papers presented at a workshop held at ANU's Research School of Pacific and Asian Studies in Canberra in January 1997"--Introduction.